تطور كتاب مادة اللغة العربية بورقة العمل لدى طلبة الصف الثاني بمدرسة القرآن بأتشيه بيسار - Moch. Fajarul Falah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
This research focuses on developing the Arabic language subject in the worksheet for students of the Qur’an Intermediate School in Aceh Besar, Indonesia. Because students do not have ample opportunities to practice what they have studied, and this makes their ability upgrade later. The two research questions are: How is the Arabic language subject in the worksheet developed? Will the worksheet be effective for improving students' ability to the Arabic language? This research uses the research and development method, using survey, interview, and testing as its research tools. And the research community is all the students in the Qur’an school and makes the second grade as the sample. As for the results of the research, they are the first. The researcher uses ten steps in development, namely, needs survey, data collection, production design and certification with experts in the field of education and learning, production improvement, his experience in the small group, production improvement, production experience in the large group, and production improvement and final products. Second, the calculated value (t-hitung) is 6 as the researcher analyzes it with a t-test related. The value in the t-tabel at the df = 28 degree of freedom and at the 5% significance level (α = 0.05) is 2,052. To achieve the hypothesis, the calculated value (t-hitung) is greater than the value in the table (t-tabel): 2,052 ≤ 6, so the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is acceptable. As the use of the worksheet is effective for improving students' understanding in learning the Arabic language. It gives a wide opportunity to practice the Arabic language for students.